Study of Exclusive Breastfeeding Problems in Postpartum Mothers and Early Neonates who experience Neonatal Jaundice - Martanti, Listyaning Eko; Ariyanti, Ida (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2025)
Introduction: The percentage of infants under 6 months of age who received exclusive breastfeeding in Indonesia in 2019-2022 was 66.99%; 69.2%, and 71.58% respectively. these figures have increased but still have not met the target.Objectives: To examine the problems of exclusive breastfeeding among postpartum mothers and early neonates at the Semarang City Hospital.Method: quantitative with an observational descriptive design. The population in this study was all mothers and babies born September - October 2023 at the Semarang City Hospital using a total sampling technique. The data obtained was then subjected to univariate analysis to see the frequency and percentage distribution of each variable.Results: The results of the univariate analysis showed that the majority of respondents were 20-35 years old (76.3%), secondary education (76.3%), primiparous parity (55.3%), not working (65.8%), baby birth weight according to the period of pregnancy (63.2%), prominent nipple shape (73.7%), birth method each SC and normal (50.0%), frequency of breastfeeding 8-12x/day (81.6%), expenditure There was little breast milk on days 1 to 3 (55.3%), little milk output on days 4 to 7 (84.2%), and no nipple pain (52.6%). The average baby bilirubin level is 15.58 mg/dL.Conclusions: It is important to inform the public about common problems that occur during the postpartum and newborn periods. The role of stakeholders is needed in developing strategies related to common problems that occur so that exclusive breastfeeding targets can be achieved.